THE ROLE OF ACCOUNTING FOR INCOME AND EXPENSES ON THE FAIRNESS OF FINANCIAL STATEMENTS AT PT HANIL JAYA STEEL IN SIDOARJO - Enny Istanti; Achmad Daengs GS (Jurnal Akuntansi dan Pajak, 2022)
To maintain business continuity, a company must be able to increase profitability and performance and a good management is needed, so management has a great responsibility for the preparation and presentation of financial statements because it involves information that will be used by related parties for decision making. This study aims to determine how the application of accounting treatment of income and expenses to the fairness of financial statements at PT Hanil Jaya Steel in Sidoarjo. The approach used in this study is a qualitative descriptive approach. In this study, the researcher uses the accrual basis method where revenue is recognized when a sale occurs. The results of this study indicate that there is still a lack of internal control carried out PT Hanil Jaya Steel in Sidoarjo in managing income and expenses